The Effect of Pressure, Opportunity, and Rationalization on the Tendency of Financial Statement Fraud: An Empirical Study on Energy Sector Companies Listed on the IDX for the Period 2020-2024 - Yohana Bate'e; Achmad Hizazi; Salman Jumaili (International Journal of Business and Quality Research, 2026)
This study aims to determine the effect of the fraud triangle, consisting of pressure, opportunity, and rationalization, on the tendency of financial statement fraud in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. The population of this study includes all 91 energy sector companies listed on the IDX. Through the purposive sampling method, 26 companies were selected as the research sample, yielding a total of 130 observations over the 5-year observation period. The data analysis technique used is multiple linear regression analysis using EViews software. The partial test results show that the pressure factor, measured by asset changes (ACHANGE) and profitability (ROA), is proven to have a significant effect on triggering the tendency of financial statement fraud. Conversely, the opportunity factor, measured by the monitoring of the independent board of commissioners (BDOUT) and company receivables (RECEIVABLES), as well as the rationalization factor, measured by the type of public accounting firm (AUDIT), do not show a significant effect on the tendency of fraud. However, when tested simultaneously, the combination of pressure, opportunity, and rationalization is proven to have a significant effect on the tendency of financial statement fraud. The results also indicate that these three factors contribute 40.845% to explaining the tendency of financial statement fraud, while the remaining percentage is influenced by other factors outside this study.